Assessment of Blocked Financial Assets in Order to Develop Measures to Support Investors - M. A. Rastorguev; A. Yu. Alеshina (Финансы: теория и практика)
The rights of Russian investors owning foreign financial assets were violated as a result of the introduction of foreign sanctions, which blocked these securities for an indefinite period. This problem is widely discussed both in the professional environment and at the state level, and a search is underway for ways to solve the current situation.   The purpose of this paper is to propose specific tools for working with blocked financial assets — assessing their value, profitability of formed portfolios, taking into account risk.   The authors have developed a model for assessing blocked foreign securities, taking into account sanctions risk, while this risk is considered a type of credit risk. As a result of implementing the model, the fair value of blocked assets is determined, which can be used to determine the value of portfolios containing blocked securities; when creating special insurance and credit products aimed at protecting the rights and income of investors, as well as when the regulator develops recommendations for assessing blocked assets for further work with them.